Work Sheet Development of High School Students Biology Based on Critical Thinking Skills on the Motion Systems Concept - Widiya Rahimah; Muhammad Zaini; Bunda Halang (Master Program of Biology Education, Universitas Lambung Mangkurat, 2020)
One of the demands in 21st-century education is critical thinking skills that are considered still lacking. The 2013 curriculum learning process includes three domains, namely affective (attitude), cognitive (knowledge), and psychomotor (skills). One of the learning tools that need to be improved to achieve the 2013 curriculum goals is LKPD. This study aims to develop a student worksheet that is valid, practical, and effective. The research method used is the Tessmer design includes expert review, one-to-one, and small group evaluation. The validation subjects were three experts, the individual test subjects were three students of class XI SMAN 6 Banjarmasin, and the smalls group test subjects were six students of class XI SMAN 6 Banjarmasin. The results showed that LKPD obtained an average score of 3.25 (valid), the practicality of the content has an average score of 3.82 (good), the practicality of expectations obtained an average score of 90.48% (very good), and the effectiveness of the expectations has a very good category and good category. The score of interpersonal skills 86.17% (very good), and scores of intrapersonal skills 84.33% (very good).AbstrakSalah satu tuntutan dalam pendidikan abad ke-21 ialah keterampilan berpikir kritis yang dianggap masih kurang. Proses pembelajaran kurikulum 2013 mencakup tiga ranah, yaitu afektif (sikap), kognitif (pengetahuan) dan psikomotorik (keterampilan). Salah satu perangkat pembelajaran yang perlu diperbaiki agar tercapai tujuan kurikulum 2013 ialah LKPD. Penelitian ini bertujuan untuk mengembangkan LKPD yang valid, praktis, dan efektif. Metode penelitian yang digunakan yaitu desain Tessmer meliputi expert review, one-to-one, dan small group evaluation. Subjek validasi adalah 3 orang ahli, subjek uji perorangan adalah 3 orang peserta didik kelas XI SMAN 6 Banjarmasin, dan subjek uji kelompok kecil adalah 6 orang peserta didik kelas XI SMAN 6 Banjarmasin. Hasil penelitian menunjukkan LKPD memperoleh skor rata-rata 3,25 (valid), kepraktisan isi memperoleh skor rata-rata 3,82 (baik), kepraktisan harapan memperoleh skor rata-rata 90,48% (sangat baik), dan keefektifan harapan memperoleh kategori sangat baik dan kategori baik. Skor keterampilan interpersonal 86,17% (sangat baik), dan skor keterampilan intrapersonal 84,33% (sangat baik).